The extent of responsibility - the seller of Alcohol or the provider – the civil towards the drug addicts and their victims "A comparative study - حسن حيدر فليح (Journal of Legal Sciences, 2019)
There are many harmful acts that occur from drunkards in this case, especially those resulting from car accidents. The world is witnessing dozens or even hundreds of car accidents due to alcohol consumption. These accidents often result in serious injuries that could lead to the death of the drunk driver and those in the car As well as other persons present in the other vehicles with which the incident occurred or pedestrians on the street, as well as damage to private or public property, and if the order of return of the affected persons on the pretext of civil liability (tort) is made as a direct cause of the harmful act, Is entitled Do they like this refer to the liquor seller or their provider as the culprit? Or are they not related to such harmful acts, especially those that are outside their premises or headquarters? And is it permissible for the drunkard himself to give them civil responsibility or not? In order to answer these questions and others, this research highlights the extent of the civil liability of the liquor seller or its provider towards the drug addicts and their victims.